Effects of Bio-based Compound Amendments on Overall Soil Fertility of Coastal Saline Soils - Huang Ting; Li Yuan; Gan Quanfeng; Hang Huixian; Su Yucheng; Zhao Gengmao (Shuitu baochi tongbao)
[Objective] The effects of bio-based composite amendments on the physicochemical properties and microbiota of saline soils in the Yellow River delta and the Northern Jiangsu mudflats were determined in order to provide a scientific reference for the improvement and utilization of saline soils in the region and for the ecological agro-pastoralism. [Methods] A pot experiment with alfalfa was conducted to study the influence of the application of compound biomaterials on the physico-chemical properties and microbial flora of coastal saline soils from the Yellow River delta (S) and the northern Jiangsu mudflats (J). The compound biomaterials consisted of vermicompost, active enzyme conditioners, and endophytic mycorrhizal inoculants. The experiment consisted of four treatments: the Yellow River delta soil with (SE) and without (SC) compound amendments, and the Northern Jiangsu tidal flat soil with (JE) and without (JC) compound amendments. [Results] Soil organic matter during the alfalfa branching stage increased by 45.30% and 32.45% in the SE and JE treatments, respectively, compared with the control treatment, and available potassium increased by 41.00% and 39.92%, respectively. Total dissolved salt in the soil during the alfalfa budding stage decreased by 14.10% and 27.85% in the SE and JE treatments, respectively, compared with the control treatment, and soil organic matter increased by 51.99% and 73.59%, respectively. Additionally, the diversity index of the soil microbial community during the budding stage was significantly increased compared with the control treatment, The dominant bacterial phyla were Proteobacteria, Bacteroidetes, Acidobacteria, Planctomycetes, and Actinobacteria. The total dissolved salt and available potassium in the soil were the main driving factors changing soil microbial community structure. [Conclusion] The bio-based compound amendments could effectively reduce the total dissolved salt in soil, increase soil available nutrients, and increase soil microbial flora, and thereby significantly improve overall soil fertility.